If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a(b + 2c) = 0 (b * 2a + 2c * 2a) = 0 (2ab + 4ac) = 0 Solving 2ab + 4ac = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), '2a'. 2a(b + 2c) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0Subproblem 2
Set the factor '(b + 2c)' equal to zero and attempt to solve: Simplifying b + 2c = 0 Solving b + 2c = 0 Move all terms containing a to the left, all other terms to the right. Add '-1b' to each side of the equation. b + -1b + 2c = 0 + -1b Combine like terms: b + -1b = 0 0 + 2c = 0 + -1b 2c = 0 + -1b Remove the zero: 2c = -1b Add '-2c' to each side of the equation. 2c + -2c = -1b + -2c Combine like terms: 2c + -2c = 0 0 = -1b + -2c Simplifying 0 = -1b + -2c The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
a = {0}
| x+3x+14=102 | | 7+3x=5+13 | | 21x-1=19x+11 | | -15x-20=-13x+120 | | X-5/7=x+3/2 | | 7(4x+1)=3x-7x | | X+5+x=19 | | -8-7=6x+9-5x | | 8x+4=7x+11 | | 3x-4-4x=6 | | 4W=-29 | | -3+quaterz=1 | | -6(v+4)+4v+6=7v+6 | | 2(5x+1)=4x-8x | | 3xx+15x-6=180 | | 4x+4+6x=64 | | 6x-3=6(x+3) | | -0.5x+7.68=-0.7x+6.48 | | 2p+9q=36 | | 16(2x-7)=4(8x+5) | | 6x+2x-5=35 | | A=a+b+c/3 | | 2(5x+6)=-33+35 | | x/10=5/12 | | x/9=36 | | 5/8x+1/16x=11/16x | | 18+10x+x^2=0 | | 2(w+5)= | | 5s+2(1/5)=3/5s+2 | | 51-3x=24x+15 | | 5x+3=14x-66 | | -9=5+2x |